The future of accessibility in disaster conditions: How wireless technologies will transform the life cycle of emergency management. (March 2017) - Bennett, DeeDee; Phillips, Brenda D.; Davis, Elizabeth
Highlights: Using Brofenbrenner's ecosystem framework the authors identify how future wireless technologies will assist emergency services personnel in their response and mitigation considering the needs of people with disabilities. The authors identify how future wireless technologies may assist emergency services personnel in their response and mitigation efforts to better consider the needs of people with disabilities. The change framework initiates from face-to-face interaction where individuals at the micro-level made a difference through their individual and household actions. This paper reveals the ways in which the broader social, political, economic, and cultural levels changed to foment a macro-level culture of safety with and for people with disabilities. Abstract: By describing a transformed life cycle of emergency management, this paper re-envisions how emergency managers may prepare for, respond to, recover from, and mitigate against disaster impacts in the future. Additionally, this paper also reveals how the broader social, political, economic, and cultural levels must change to foment a culture of safety with and for people with disabilities. The authors use the framework to identify how future wireless technologies can empower people with disabilities with regards to individual (or household) emergency preparedness and in coping with the drastic life changes following a disaster.